ANALISIS KESALAHAN PESERTA DIDIK KELAS XI SMA NEGERI 3 PADANG DALAM MENYELESAIKAN SOAL PEMECAHAN MASALAH MATEMATIS BERDASARKAN TAHAPAN NEWMAN - Mumtaza, Nurul (Departemen Matematika, 2023)
Mathematics is one of the crucial subjects to increase the skills of problem solving in mathematical of high school (SMA) students. However, there are still many students who make false in solving mathematical problem solving questions. The research purpose was to describe students' mistakes in solving mathematical problem solving questions and to look the factors that why students to make false in solving mathematical problem solving questions. This research type is descriptive research using a qualitative approach. The techniques for data collection used in this research were mathematical problem solving tests and semi-structured interviews. The research subjects were students of class XI SMA Negeri 3 Padang. The results showed that there were 5 mistakes made by students in solving mathematical problem solving questions according to Newman's error analysis, namely (1) reading, 21% of students who make this error; (2) comprehension, 31% of students who carry out error; (3) transformation, 37% of students who carry out error; (4) process skill, 47% of students who carry out error and; (5) encoding, 54%. The errors type made by high group subjects in general were process skill and encoding. The types of errors that were made by the subject of the medium group in general were transformation, process skills, and encoding. The errors types made by the low group subjects were comprehension, transformation, process skill, and encoding.Keywords – Mathematical Problem Solving Ability, Newman’s Error Analysis